Elucidating the Effect of Mass Transport Resistances on Hydrogen Crossover and Cell Performance in PEM Water Electrolyzers by Varying the Cathode Ionomer Content. Issue 8 (1st January 2019) - Trinke, P.; Keeley, G. P.; Carmo, M.; Bensmann, B.; Hanke-Rauschenbach, R.
Abstract : An important challenge for polymer electrolyte membrane (PEM) water electrolysis is to reduce the permeation of the produced gases. This crossover affects the cell efficiency and causes safety issues. The crossover increases with current density, most probably due to mass transfer resistances. This work aims to investigate the influence of the cathode ionomer content on hydrogen crossover. Therefore, the ionomer content was varied between 10 and 40 wt% to clearly influence the mass transfer resistances. The best performance and lowest crossover was obtained for 10 wt% ionomer. However, within the observed ionomer range the mass transfer resistances increase with ionomer content that cause increases in hydrogen crossover and cell voltage. Both can be entirely explained by the same quantity of supersaturated dissolved hydrogen concentrations. These supersaturated concentrations cause higher cathode half-cell potentials, which explain the cell voltage increase and lead to higher concentration gradients across the membrane, which enhance the crossover. These findings highlight the importance of mass transfer resistances within catalyst layers in terms of crossover and performance. They constitute an important step in the clarification of the complex interplay between mass transport and voltage losses, enabling the development of novel electrode architectures for PEM water electrolyzers.